An assessment of the nocturnal insect diversity and abundance between an agricultural and suburban landscape in Peninsular Malaysia - Nur Atiqah Abd Rahman,; Siti Nurul Amirah Md Dujali,; Hafizzudin Abdul Rahim,; Salmah Yaakop,; Ng, Yong Foo; Jin, Sia Ting; Asraf Bakri,; Zubaid Akbar Mukhtar Ahmad, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
A total of 46, 912 insects comprising 112 families from 14 orders were collected with light traps. The agricultural landscape had higher insect abundance compared to the suburban landscape where there were 27, 833 insect individuals belonging to 96 families and 19, 079 insect individuals belonging to 75 families respectively. The four most abundant orders collected at the agricultural landscape were Coleoptera followed by Hymenoptera, Hemiptera and Isoptera while at the suburban landscape were Hymenoptera followed by Coleoptera, Isoptera and Hemiptera. Eventhough the similarity index was 67.8% there was no significant difference in insect abundance between both sampling sites (P= 0.622, p > 0.05). The Shannon-Weiner diversity index at the agricultural landscape (H’ =2.581) was higher compared to the suburban landscape (H’ = 2.422). However, the evenness at the suburban landscape (EH = 0.1502) was higher compared to the agricultural landscape (EH = 0.1376). The data obtained provides baseline information on nocturnal insect availability and activity in anthropogenically altered habitats which will be of use when studying foraging habits of nocturnal aerial insectivores and in insect pest control.